2012
DOI: 10.1177/0961203312439335
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of antiphospholipid antibody assays. Where do we stand?

Abstract: The laboratory criteria (lupus anticoagulants (LA), and/or anti-cardiolipin (aCL) antibodies and/or anti-b2-glycoprotein I antibodies (ab2GPI)) that define patients with antiphospholipid syndrome (APS) were set in the Sapporo and Sydney criteria published in 1999 and 2006, respectively, and led to a substantial improvement in the recognition of APS. In addition, guidelines for LA detection were published by the Scientific Standardisation Subcommittee (SSC) of the International Society of Thrombosis and Haemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 23 publications
1
65
0
4
Order By: Relevance
“…A major problem within APS is the variability between different commercial anti-β 2 GPI available assays [2], [12], [13], [14]. External quality Control of diagnostic Assays and Tests Disagreement (ECAT) reports showed that laboratories obtain good results for negative or clearly positive samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major problem within APS is the variability between different commercial anti-β 2 GPI available assays [2], [12], [13], [14]. External quality Control of diagnostic Assays and Tests Disagreement (ECAT) reports showed that laboratories obtain good results for negative or clearly positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…A major problem within APS is the variability between different commercially available assays [2], [12], [13], [14]. In other words, a sample assigned positive in one test does not automatically test positive in the same type of assay from a different manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large variety of assays assessing aPL and despite consensus guidelines, some issues remain unanswered [2]. Factors that contribute to result variability include pre-, post-and analytical conditions, calibration and assay-specific issues [3].…”
Section: Introductionmentioning
confidence: 99%
“…Issues such as antibody heterogeneity, between‐reagent and between‐platform variability, and differences in raw data manipulation and interpretation, conspire to make standardization an elusive goal. Consequently, gold standard assays and reference plasmas are not yet established 4, 5. While aCL and aβ2GPI assays can be calibrated to generate quantitative results in semi‐arbitrary units to aid interpretation, a medley of phospholipid‐dependent coagulation assays are employed for LA detection and the presence of LA is inferred or excluded from the result patterns obtained.…”
Section: Introductionmentioning
confidence: 99%